STUDI PEMIKIRAN MESTIKA ZED TENTANG PEMERINTAH DARURAT REPUBLIK INDONESIA - Erasiah Erasiah (Buletin Al-Turas, 2019)
The Emergency Government of the Republic of Indonesia is a legitimate government that is run by car or moves from one place to another during the emergency period of the Republic of Indonesia due to the second Dutch military attack. This research is carried out through library studies whose sources are found in books, both primary and secondary sources. As the primary source is Mestika Zed's work entitled Some Where in the Jungle Emergency Government of the Republic of Indonesia: A Forgotten History Chain, West Sumatra in the History Stage 1945-1995, Indonesia in the Flow of History. While secondary sources are books and articles that talk about the Emergency Government of the Republic of Indonesia. The method used in this study is a historical research method with four steps of work, namely heuristics (collecting resources), source criticism, synthesis, and writing. While the theory used to analyze Mestika Zed's thinking about the Republic of Indonesia Emergency Government is the theory of historical explanation theory of Kuntowijoyo. Kuntowijoyo said that the historical explanation has three important things (historical explanations are hermeneutic and verstehen, historical explanations are explanations of limited elongated time in space, and historical explanations are explanations of single events).